Effects of drought stress on physiological-biochemical characteristics and anatomical structure of Camellia reticulata and C. sasanqua seedlings: a comprehensive evaluation - Yan, Fu-Jun; Huang, Yuan-Yuan; Zhang, Zhi-Yu; Xiao, Hong-Xing; Wu, Xue-Qin; Wu, Yun-Long; Wang, Zhong-Lang; Geng, Fang (Frontiers in Plant Science, 2025)
The cultivation and landscaping use of camellias, a valuable woody ornamental, is constrained by its sensitivity to water stress, limiting its adaptability and increasing upkeep expenses. This study investigated the effects of drought stress on leaf anatomical structures and physiological-biochemical indicators in three-year-old seedlings of Camellia reticulata and C. sasanqua. Seedlings of both camellias were cultivated in 3-gallon nursery pots filled with a 1:1 mixture of red soil and humus soil. The experiment was conducted in a plastic greenhouse maintained at 18 - 28 °C. Drought stress was imposed using the pot water-controlled method, with stress durations of 0, 4, 8, 12, and 16 days. As drought stress intensified, significant phenotypic differences emerged between the two camellias, accompanied by notable changes in leaf tissue structure and physiological-biochemical parameters. Drought differentially affected the stomata of both camellias. Under moderate and severe stress conditions, leaf thickness decreased significantly, with partial stomata closure observed under severe drought. The content of osmoregulatory substances — including soluble sugars, soluble proteins, and proline — increased markedly in both camellias. Concurrently, the activity of antioxidant enzymes exhibited an upward trend, indicating the activation of active defense and adaptation mechanisms under adverse conditions. Finally, comprehensive evaluation of drought tolerance using the subordinate function method and principal component analysis (PCA) yielded scores of D = 0.338 for C. reticulata and D = 0.551 for C. sasanqua. These results demonstrate that C. sasanqua exhibits significantly stronger drought resistance than C. reticulata.